Silencing of circ_0000205 mitigates interleukin-1β-induced apoptosis and extracellular matrix degradation in chondrocytes via targeting miR-766-3p/ADAMTS5 axis. Issue 2 (February 2022) - Li, Guowen; Luo, Heyuan; Ding, Zhiyong; Liang, Haofeng; Lai, Zhoupeng; Chen, Shuzhen; Huang, Yuliang
The aim of this study was to explore the role of hsa_circRNA_0000205 (circ_0000205) in chondrocyte injury in osteoarthritis (OA) and the underlying mechanism. Expression of circ_0000205, microRNA (miR)-766-3p and a disintegrin and metalloproteinase with thrombospondin motif (ADAMTS)-5 was detected by quantitative real time (qRT)-polymerase chain reaction (PCR) and Western blot assays. Cell proliferation, apoptosis, and extracellular matrix (ECM) synthesis were examined by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide and 5-ethynyl-2-deoxyuridine assays, flow cytometry, and qRT-PCR and Western blot assays. The target relationship between miR-766-3p and circ_0000205 or ADAMTS5 was confirmed by luciferase reporter assay and RNA immunoprecipitation. IL-1β treatment could attenuate cell viability of primary chondrocytes and proliferating cell nuclear antigen (PCNA) and collagen II type alpha-1 (COL2A1) levels, and elevate apoptosis rate and cleaved caspase-3, ADAMTS5 and matrix metalloproteinase-13 (MMP13) levels, suggesting that IL-1β induced chondrocyte apoptosis and ECM degradation. Expression of circ_0000205 was up-regulated in OA tissues and IL-1β-induced primary chondrocytes, accompanied with miR-766-3p down-regulation and ADAMTS5 up-regulation. Knockdown of circ_0000205 could mitigate IL-1β-induced above effects and improve cell proliferation. Moreover, both depleting miR-766-3p and promoting ADAMTS5 could partially counteract circ_0000205 knockdown roles in IL-1β-cultured primary chondrocytes. Notably, circ_0000205 was verified as a sponge for miR-766-3p via targeting, and ADAMTS5 was a direct target for miR-766-3p. Silencing circ_0000205 could protect chondrocytes from IL-1β-induced proliferation reduction, apoptosis, and ECM degradation by targeting miR-766-3p/ADAMTS5 axis.